Case Report: The novel hemizygous mutation in the SSR4 gene caused congenital disorder of glycosylation type iy: A case study and literature review - Wang, Jun; Gou, Xingqing; Wang, Xiyi; Zhang, Jing; Zhao, Nan; Wang, Xiaohong (Frontiers in Genetics, 2022)
Background: Recently, the hemizygous variation of SSR4 gene has been reported to be associated with congenital disorder of glycosylation type Iy. To date, only 13 patients have been diagnosed with SSR4-CDG in the worldwide, but it has not been reported in the Chinese population. Methods: Whole-exome sequencing and gene copy number variation analysis were used to genetic analysis. The mRNA expression of SSR4 gene in blood was detected by Real-time Quantitative PCR. The clinical manifestations of all patients reported in the literature were reviewed. Results: WES analysis identified a de novo hemizygous variant c.269G>A (p.Trp90*) of SSR4 gene in the proband with psychomotor retardation, microcephaly, abnormal facial features, and nystagmus. This variant has not been reported in previous studies. The in vivo mRNA expression of SSR4 gene in patient was significantly decreased. Literature review showed that all 14 patients, including our patient, presented with hypotonia, intellectual disability, developmental delay, microcephaly, and abnormal facial features, while most patients had feeding difficulties, growth retardation, and ocular abnormalities, and epilepsy and skeletal abnormalities are less common. Conclusion: We reported the first case of SSR4-CDG caused by SSR4 variant in Chinese population, expanded the clinical and mutation spectra of the disorder, clarified the genetic etiology of the patient, and offered support for the prenatal diagnosis of the index family.